EKSPLORASI PERAN KBBI DARING SEBAGAI SUMBER RUJUKAN LEKSIKAL BAGI MAHASISWA PENDIDIKAN BAHASA DAN SASTRA INDONESIA - Nurul Hijrah; Amira Syifani; Diva Azzurra Putri Rialni; May sarah; Rika Arini (Pendidikan Bahasa dan Sastra Indonesia, 2025)
The development of information technology has transformed the landscape of language education, making the Online Great Dictionary of the Indonesian Language (KBBI) a vital digital lexicography tool. This study aims to analyze the role, usage patterns, and limitations of the Online KBBI as a lexical reference source for students of the Indonesian Language and Literature Education Study Program (PBSI). This study uses a qualitative descriptive method with purposive sampling techniques on students who actively use the Online KBBI for academic purposes. The results show that the Online KBBI plays a strategic role as a validator of word standardization, spelling, and meaning in scientific writing. However, significant limitations were also found related to network accessibility, delays in updating new terms, and definitions that are sometimes too concise for in-depth analysis. Therefore, optimization is needed through routine integration in learning and digital literacy training so that the Online KBBI is not only used for quick searches, but also as a comprehensive language learning medium.